2018
DOI: 10.3389/fphar.2018.01087
|View full text |Cite
|
Sign up to set email alerts
|

PAI-1 Exacerbates White Adipose Tissue Dysfunction and Metabolic Dysregulation in High Fat Diet-Induced Obesity

Abstract: Background: Plasminogen activator inhibitor (PAI)-1 levels and activity are known to increase during metabolic syndrome and obesity. In addition, previous studies have implicated PAI-1 in adipose tissue (AT) expansion while also contributing to insulin resistance. As inflammation is also known to occur in AT during obesity, we hypothesized that in a high-fat diet (HFD)-induced obese mouse model PAI-1 contributes to macrophage-mediated inflammation and metabolic dysfunction.Methods: Four- to five-weeks-old male… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
36
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(38 citation statements)
references
References 35 publications
2
36
0
Order By: Relevance
“…PAI-1 is mainly produced within white adipose tissue, with adipocytes being the major source of production for circulating PAI-1 in obese individuals. Previous studies have revealed that PAI-1 deficiency protects against obesity and metabolic dysfunction [2,7]. Indeed, our recent study demonstrated that genetic deletion and pharmacological inhibition of PAI-1 improve glucose tolerance and insulin sensitivity [2], which was supported by reduced inflammation and macrophage infiltration into WAT.…”
Section: Introductionmentioning
confidence: 66%
See 2 more Smart Citations
“…PAI-1 is mainly produced within white adipose tissue, with adipocytes being the major source of production for circulating PAI-1 in obese individuals. Previous studies have revealed that PAI-1 deficiency protects against obesity and metabolic dysfunction [2,7]. Indeed, our recent study demonstrated that genetic deletion and pharmacological inhibition of PAI-1 improve glucose tolerance and insulin sensitivity [2], which was supported by reduced inflammation and macrophage infiltration into WAT.…”
Section: Introductionmentioning
confidence: 66%
“…Previous studies have revealed that PAI-1 deficiency protects against obesity and metabolic dysfunction [2,7]. Indeed, our recent study demonstrated that genetic deletion and pharmacological inhibition of PAI-1 improve glucose tolerance and insulin sensitivity [2], which was supported by reduced inflammation and macrophage infiltration into WAT. Further supporting a relationship between PAI-1 and metabolism, an increased release of cytokines has been linked to PAI-1 expression in human adipose tissue explants and obese mice.…”
Section: Introductionmentioning
confidence: 66%
See 1 more Smart Citation
“…Other differences between the two types of adipose tissues are the depot localization, profile of secreted molecules, cell population, vascularization and also innervation [2][3][4]. While both of these adipose tissue groups contribute a significant role in maintaining systemic homeostasis, WAT is the primary site of metabolic dysregulation in many metabolic diseases [5,6].…”
Section: The Adipose Tissue 21 Adipose Heterogeneitymentioning
confidence: 99%
“…PAI‐1 is the main inhibitor for fibrinolysis. PAI‐1 plays an important role in the pathogenesis of arterial and venous thrombosis at high concentrations, and has been associated with obesity, insulin resistance, diabetes and premature aging 12‐14 . All of these conditions are common in patients with COPD 15,16 .…”
Section: Introductionmentioning
confidence: 99%